Enhanced inhibitory control during reengagement processing in badminton athletes:An event-related potential study - Chen, J.; Li, Y.; Zhang, G.; Jin, X.; Lu, Y.; Zhou, C. (Journal of Sport and Health Science, 2019)
Purpose: The purpose of present study was to investigate the impact of sport experience on response inhibition and response re-engagement in expert badminton athletes during the stop-signal task and change-signal task. Methods: A total of 19 badminton athletes and 20 nonathletes performed both the stop-signal task and change-signal task. Reaction times (RTs) and event-related potentials were recorded and analyzed. Results: Behavioral results indicated that badminton athletes responded faster than nonathletes to go stimuli and to change signals, with faster change RTs and change-signal RTs, which take into consideration the variable stimulus onset time mean. During successful change trials in the change-signal task, the amplitudes of the event-related potential components N2 and P3 were smaller for badminton athletes than for nonathletes. Moreover, change-signal RTs and N2 amplitudes as well as change RTs and P3 amplitudes were significantly correlated in badminton athletes. A significant correlation was also found between the amplitude of the event-related potential component N1 and response accuracy to change signals in badminton athletes. Conclusion: Moderation of brain cortical activity in badminton athletes was more associated with their ability to rapidly inhibit a planned movement and reengage with a new movement compared with nonathletes. The superior inhibitory control and more efficient neural mechanisms in badminton athletes compared with nonathletes might be a result of badminton athletes` professional training experience.